Defending and Strengthening Public Education as a Common Good: Toward Cross-Border Advocacy - Moore, Shannon Dawn Maree; Yoon, Ee-Seul; Janzen, Melanie D. (Critical Education, 2024)
For decades, there has been a well-coordinated effort to unmake public education in Canada and around the globe. Neoliberal reformers have undermined public education through increased privatization, marketization, and managerialism. Government austerity measures have shaped policy that falsely necessitates, validates, and legitimizes the privatization of public education. All of these forces that fuel the neoliberal reform movement diminish the collective aims, benefits, and responsibility of/for public education. Instead, the movement encourages systems that ration education. The moves to emulate business models in education systems exacerbate inequities and run counter to the purpose of public education. Indeed, attempts to marketize, commodify, privatize, and dismantle public education are well-organized and coordinated. Yet, in Canada, provincial and territorial fragmentation has veiled the well-organized rhetoric and tactics of neoliberal education reforms. As a result, community and political responses have often been confined within borders. The reformers have been centrally organized, but the resistance has not. Recognizing that provincial and territorial borders can act as barriers to collective advocacy, this special issue is intended to share activities, research, and writing from across Canada about the tactics and impacts of privatization, to recognize the efforts being made to organize a collective response to privatization efforts, and to encourage national conversations beyond borders.